Questions of Education and Psychology - Koniushenko S. M., Komissarova M. O., Temirkanova T. E., Iusupova A. M., Gaparova C. A., Madumarova M. K., Bekmurzaeva B. A., Orunbaev T. A., Zhaloobek kyzy M., Abdimomunova A. O., Biinazarova N. S., Esenalieva S. T., Kulemina K. V., Fedorova O. V., Danilchenko S. L., Popova R. I., Chetina M. M., Sudakov D. V., Sudakov O. V., Gordeeva O. I., Piatibratova I. V., Aleksina T. V., Iakusheva O. V., Krasnopiorova A. G., Khomova N. A., Sannikova S. V., Frolova N. K., Kogut A. A., Pilipenko A. R., Groza A. B., Bakhtiurina L. A., Pozdnyakov A. N. (Questions of Education and Psychology, 2024)
the chapter considers the problem of formation of ecological culture of citizens, analyzes the effectiveness of the ecological festival as an innovative method of environmental education. In the course of the work, sociological methods (surveys, reviews, interviewing), analysis of statistical data were used. The success of the annual ecological family festival «ArtLuga», held in Artemovsk meadows on the banks of the Volga River, is presented. Examples of filling the events of the festival held in 2024, «ArtLuga – Dawn», are given. The chapter can be used as a small guide that gives vectors for thinking through a festival of this format with an ecological and educational bias.
Keywords: экологическое сознание; environmental education; экологическое просвещение; экофестиваль; Артемовские луга; environmental awareness; ecofestival; Artemivskie meadows